Chest decompression during the resuscitation of patients in prehospital traumatic cardiac arrest. Issue 10 (22nd September 2009) - Mistry, N; Bleetman, A; Roberts, K J
Abstract : Background: Tension and bilateral pneumothorax can cause or contribute to death following trauma. A surgical incision (thoracostomy) or needle decompression through the chest wall rapidly treats these conditions. Resuscitation of patients in traumatic cardiac arrest focuses on treating common and reversible life-threatening conditions. A study was undertaken to observe the practice, findings and outcome of chest decompression when performed as part of the resuscitation strategy of these patients by air ambulance crews. Methods: Patients in prehospital traumatic cardiac arrest were identified over a 39-month period from an air ambulance database. The use of thoracostomy or needle decompression was identified together with indications, findings and outcome. Primary outcome was return of cardiac output by arrival at hospital. Results: 18 of 37 cases underwent chest decompression (17 thoracostomy, 1 needle decompression). Four patients had a return of cardiac output (3 tension pneumothorax, 1 bilateral pneumothorax). Six further cases were positive for intrathoracic injury. In 2 cases the injuries identified were incompatible with life and resuscitation efforts were consequently ceased. Conclusions: Chest decompression in traumatic cardiac arrest identifies and treats a high proportion of potentially life-ending injuries and should be considered as part of the resuscitation effort of patients in traumatic cardiac arrest. In a proportion of patients, non-survivable injuries are identified which guide resuscitation efforts.